DNA adducts of antitumor trans-[PtCl2 (E-imino ether)2] - Brabec, V; Vrána, O; Nováková, O; Kleinwächter, V; Intini, F P; Coluccia, M; Natile, G (Nucleic acids research, 1996)
It has been shown recently that some analogues of clinically ineffective trans-diamminedichloroplatinum (II) (transplatin) exhibit antitumor activity. This finding has inverted the empirical structure-antitumor activity relationships delineated for platinum(II) complexes, according to which only the cis geometry of leaving ligands in the bifunctional platinum complexes is therapeutically active. As a result, interactions of trans platinum compounds with DNA, which is the main pharmacological target of platinum anticancer drugs, are of great interest. The present paper describes the DNA binding of antitumor trans-[PtCl(2)(E-imino ether)(2)] complex (trans-EE) in a cell-free medium, which has been investigated using three experimental approaches. They involve thiourea as a probe of monofunctional DNA adducts of platinum (II) complexes with two leaving ligands in the trans configuration, ethidium bromide as a probe for distinguishing between monofunctional and bifunctional DNA adducts of platinum complexes and HPLC analysis of the platinated DNA enzymatically digested to nucleosides. The results show that bifunctional trans-EE preferentially forms monofunctional adducts at guanine residues in double-helical DNA even when DNA is incubated with the platinum complex for a relatively long time (48 h at 37 degrees C in 10 mM NaCIO(4). It implies that antitumor trans-EE modifies DNA in a different way than clinically ineffective transplatin, which forms prevalent amount of bifunctional DNA adducts after 48 h. This result has been interpreted to mean that the major adduct of trans-EE, occurring in DNA even after long reaction times, is a monofunctional adduct in which the reactivity of the second leaving group is markedly reduced. It has been suggested that the different properties of the adducts formed on DNA by transplatin and trans-EE are relevant to their distinct clinical efficacy.
Keywords: ethidium; Cattle; denaturace nukleových kyselin; adukty DNA; Fluorescent Dyes; Thiourea; Structure-Activity Relationship; Molecular Probes; skot; Organoplatinum Compounds; thiomočovina; Ethidium; Nucleic Acid Denaturation; vztahy mezi strukturou a aktivitou; deoxyguanosin; Animals; DNA Adducts; zvířata; molekulární sondy; fluorescenční barviva; DNA; cisplatina; organoplatinové sloučeniny; Cisplatin; Deoxyguanosine